Air blast response of compaction foam having a deformable front face panel incorporating fluid structure interactions. (January 2016) - Turkyilmazoglu, Mustafa
Abstract: The present work is devoted to derive an analytical solution to the air blast response of dynamic compaction process of a sandwich composite containing a deformable front face and a cellular core. Shock wave model in association with the mass conservation and Newton׳s second law are employed to solve the problem. Both the weak fluid-structure interactions (FSI) such as those that are thought to occur due to air blast loading and the non-FSI cases are discussed and the results are compared with those available in the literature. The main contribution of this paper is that without having to numerically solve the governing equations, the form of the analytical solutions is capable of explaining the behaviour of enhancement zone for different choices of models including non-FSI, KNR (Kambouchev Noels Radovitzky) and FSI, which has potential advantages in practical applications. For instance, according to the results, the initial velocity of the face plate against the blast load will deter the cellular core compaction, which is basically the idea behind the "active armor". Therefore, the model developed in this paper may provide useful information for the design of such armor structures. Abstract : Highlights: The crushed cellular core may be subjected to any type of decaying impulsive loading. Fluid structure interactions (FSI) are taken into account. The engineering quantities of cellular layer are analytically computed. The KNR model is also covered by the derived solutions. A mechanism to initiate opposite motion of the front face plate would be desirable.